2011
DOI: 10.1007/s13346-011-0015-5
|View full text |Cite
|
Sign up to set email alerts
|

The use of bone cement for the localized, controlled release of the antibiotics vancomycin, linezolid, or fusidic acid: effect of additives on drug release rates and mechanical strength

Abstract: Bone cement containing antibiotics is commonly used to treat orthopedic related infections. However, effective treatment (especially of resistant bacteria, methacillin-resistant Staphylococcus aureus (MRSA)) is compromised by very low levels of drug release so that typically less than 10% of loaded drug is released over a 6-week period. The objective of this study was to investigate the effect of incorporation of water soluble excipients (polyethylene glycol, sodium chloride, or dextran) into antibiotic-loaded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 42 publications
2
21
0
Order By: Relevance
“…Because DOX and 5FU only released small amounts of drug from the LDH clay, these LDH/drug complexes were not included in film studies. VAN and SF only bound weakly to the LDH clays, but these drugs are particularly effective against drug-resistant bacteria, which represent a increasing problem in hospital settings [17]. By incorporating these drugs in LDH claypolymer film formulations, we have demonstrated that antimicrobial activity can be preserved over longer durations (Table 1).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Because DOX and 5FU only released small amounts of drug from the LDH clay, these LDH/drug complexes were not included in film studies. VAN and SF only bound weakly to the LDH clays, but these drugs are particularly effective against drug-resistant bacteria, which represent a increasing problem in hospital settings [17]. By incorporating these drugs in LDH claypolymer film formulations, we have demonstrated that antimicrobial activity can be preserved over longer durations (Table 1).…”
Section: Discussionmentioning
confidence: 93%
“…We have previously reported that the drugs VAN, SF, and ASO are stable for extended periods in aqueous environments [17,23] whereas commonly used antibiotics erythromycin, cefazolin and TET are rapidly degraded in water. In this study TET was retained in the non-degraded form when bound to clay, despite prolonged incubation in water.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, options of adding additives to improve antibiotic release without compromising the mechanical strength of bone cement have been reported. Jackson et al demonstrated that the addition of sodium chloride and dextran into bone cement improved drug release while maintaining mechanical strength [58].…”
Section: Infectionmentioning
confidence: 99%
“…Polymethylmethacrylate (PMMA) bone cements used clinically for implant fixation, kyphoplasty, [266] and bone augmentation, [267] exhibit very poor control over entrapped dose release kinetics, often leaving up to 40% of the drug trapped in PMMA. [268,269] Injectable CPC exhibits several unique properties for bone drug delivery, including peri-operative preparation and drug loading, liquid-solid setting in situ, intrinsic osteoconductivity (degradable by osteoclasts), osteoinductivity (infiltrated by osteoblasts and replaced with new bone), and acceptable biocompatibility. [270][271][272] CPC's self-setting ability at ambient or body temperature within the bone cavity [273] enables injectable formulation, largely expanding its therapeutic utility.…”
Section: Challenges and Strategiesmentioning
confidence: 99%